Nurses', patients', and informal caregivers' attitudes toward aggression in psychiatric hospitals: A comparative survey study - Välimäki Maritta; Lam Joyce; Bressington Daniel; Cheung Teris; Wong Wai Kit; Cheng Po Yee Ivy; Ng Chi Fai; Ng Tony; Yam Chun Pong; Ip Glendy; Paul Lee; Lantta Tella (Public Library Science, 2025)
Attitudes toward aggression is a controversial phenomenon in psychiatry. This study examined and compared attitudes toward patient aggression in psychiatric hospitals from the perspectives of nurses, patients and informal caregivers and identified factors associated to these attitudes. A total of 2,424 participants completed a self-reported instrument regarding attitudes toward aggression (12-items Perception of Aggression Scale; POAS-S). We analysed data from nurses (n = 782), patients (n = 886), and informal caregivers (n = 765). Pearson's rcorrelations were used to examine associations between variables. Differences between group scores were analysed using ANOVA/MANOVA with post-hoc Sheffe tests. Multivariate logistic regression models and logistic regression analysis were used to examine the effects of respondents' characteristics on their attitudes toward aggression. Nurses had significantly more negative and less tolerant perceptions toward aggression (mean [SD] 47.1 [7.5], p<0.001) than the patients (mean [SD] 44.4 [8.2]) and the informal caregivers (mean [SD] 45.0 [6.9), according to the POAS-S total scores. The same trend was found with the dysfunction and function sub-scores (mean [SD] 25.3 [4.1] and 15.0 [3.6], respectively); the differences between the groups were statistically significant (p <0.001) when nurses' scores were compared to those of both the patients (mean [SD] 23.7 [5.3] and 14.0 [4.1], respectively) and the informal caregivers (mean [SD] 24.4 [4.2] and 13.9 [3.5], respectively). The study offers new understanding of aggressive behavior in different treatment settings where attitudes toward patient behavior raises ethical and practical dilemmas. These results indicate a need for more targeted on-the-job training for nursing staff, aggression management rehabilitation programs for patients, and peer-support programs for informal caregivers focused on patient aggression.